2023
DOI: 10.1186/s12887-023-04419-x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of malnutrition among critically ill children: a systematic review and meta-analysis

Eyob Girma Abera,
Habtamu Sime

Abstract: Background Critically ill children have a lower nutritional reserve, compounding the restricted food intake during intensive care unit (ICU) and hospital stays, and scarce data are available to point out the problem. Therefore, this review aimed to assess the pooled prevalence of malnutrition among critically ill children. Methodology This systematic review was conducted in accordance with the JBI methodology for systematic reviews of prevalence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Our study on patients with CNI in our institution showed that 12% of the patients were diagnosed as underweight, 22.5% exhibited signs of chronic malnutrition, and 8% were classified as acute malnutrition ( Table 1 ). These results align with previously published reports of a ~20–30% prevalence of malnutrition in developed countries [ 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study on patients with CNI in our institution showed that 12% of the patients were diagnosed as underweight, 22.5% exhibited signs of chronic malnutrition, and 8% were classified as acute malnutrition ( Table 1 ). These results align with previously published reports of a ~20–30% prevalence of malnutrition in developed countries [ 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…It has a far-reaching impact on a child's physical and cognitive development [4,5]. Malnourished children have an increased risk of infectious and non-communicable diseases, and long-term sequelae include delayed mental development, poor school performance, and reduced intellectual capacity [6][7][8]. These impacts can extend into adulthood, affecting work capacity, causing reduced economic productivity and income, and intergenerational transmission of poverty and poor health [5,6].…”
Section: Introductionmentioning
confidence: 99%